2005
DOI: 10.3928/01484834-20051201-06
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of a Healthy-Lifestyle-Promoting Program for Nursing Students in Taiwan

Abstract: This pilot study evaluated the effects of a healthy-lifestyle-promoting program, taught as part of an undergraduate community health nursing course, on the physical fitness and health choices of 42 Taiwanese nursing students. A convenience sample provided quantitative indexes of physical fitness and lifestyle before and after the course. Qualitative data, in the form of student diaries, were also analyzed. The findings indicated a positive change in physical fitness, exercise, and nutrition as a result of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 7 publications
2
22
1
1
Order By: Relevance
“…The difference in the scores of the experimental and control groups was significant in relation to type of diet and nutritional habits but was not significant in relation to physical activity. This result supports the results of many of the reviewed studies [21][22][23][24] and might be attributed to that it is easier to note the direct influence on behaviours that do not require much effort such as nutrition vs. behaviours related to physical activity. However, the results of a study conducted in Beijing reflected contradictory results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The difference in the scores of the experimental and control groups was significant in relation to type of diet and nutritional habits but was not significant in relation to physical activity. This result supports the results of many of the reviewed studies [21][22][23][24] and might be attributed to that it is easier to note the direct influence on behaviours that do not require much effort such as nutrition vs. behaviours related to physical activity. However, the results of a study conducted in Beijing reflected contradictory results.…”
Section: Discussionsupporting
confidence: 87%
“…At the university, the results of a pilot study to evaluate the effects of a healthy-lifestyle-promoting programme, taught as part of an undergraduate community health nursing course, indicated a positive change in physical fitness, exercise and nutrition among students. 22 Similarly, a study conducted in Taiwan indicated that a course on health promotion for nursing students significantly increased students' intent to adopt healthy lifestyles. 23 In Lebanon, a positive impact of a universitylevel 'Health Awareness' course on attitudes and behaviours of undergraduates enrolled in the course was reported.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent findings have correlated nutritional habits, obesity, and lack of sleep (Yeh, Chen, Wang, Wen, & Fetzer, 2005). In a study conducted by Spivey (2010), sleeping 5 or fewer hours per night caused a greater risk in weight gain as compared with sleeping for 7-8 hr per night.…”
Section: Sleepmentioning
confidence: 99%
“…Internal consistency for the total scale was 0AE93 and for the subscales ranged from 0AE68 to 0AE86 (Huang & Chiou 1996). The Chinese version HPLP has been used with 122 postpartum Taiwanese women (Chen et al 2007), 129 outpatients with lupus erythematosus (Huang et al 2007), and 42 female senior nursing students (Yeh et al 2005).…”
Section: Background Health Promoting Lifestyle Profilementioning
confidence: 99%